Quality of Emergency Complaint Services Call Center 112 Sidoarjo Regency - Nabilah Izzati Zaewari; Indira Arundinasari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to analyze the quality of emergency complaint services through the 112 Call Center in Sidoarjo Regency. This service serves as the primary channel for the public to report emergencies related to safety, security, and order. The study used a descriptive qualitative approach through document study and observation. Callers were categorized into four types: normal, information, ghost, and prank. Analysis of service quality using the five dimensions of Zeithaml, Parasuraman, and Berry, namely physical evidence, reliability, responsiveness, assurance, and empathy, showed that the infrastructure was adequate, officers were professional and responsive, and showed empathy towards callers. However, there is still misuse of services and low public understanding of the function of emergency services. Improving service quality through call screening mechanisms, human resource training, and public education is needed to make services more effective and targeted. The results of the study confirm that the 112 Call Center plays a strategic role in supporting effective, responsive, and safety-focused public services.